Diagnostic Sensitivity of Different Applications of Pathergy Test for Behçet’s Disease - İncilay KALAY YILDIZHAN,; Ayse BOYVAT, (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the sensitivity of the intradermal application of the pathergy test with the “three-step pathergy test”. Patients and methods: The study included 60 patients with Behçet's disease (BD) (23 males, 37 females; mean age 33.9±9.7 years; range, 11 to 57 years) and 100 patients with recurrent aphthous stomatitis as the control group (39 males, 61 females; mean age 32.4±12.1 years; range, 11 to 66 years). Simultaneous intradermal pathergy test and three-step pathergy test were applied to each patient. Results: Twenty-six patients (43.3%) with BD had positive three-step pathergy test and 18 (30%) of them had positive intradermal pathergy test. A statistically significant relationship was found between the three-step pathergy test positivity and male sex while no relationship was detected between the disease activity and the positivity of the pathergy test. In the three-step pathergy test, pathergy positivity with intramuscular method was statistically significantly higher than with intravenous method. Conclusion: The three-step pathergy test in patients with BD was found to have higher sensitivity compared with the intradermal pathergy test. The intramuscularly applied pathergy test was the main cause of increase in sensitivity. Further studies are needed to develop new applications of pathergy test that would increase the sensitivity and which are also easy to apply.